2021
DOI: 10.3389/fphar.2021.651790
|View full text |Cite
|
Sign up to set email alerts
|

Current Bioequivalence Study Designs in South Korea: A Comprehensive Analysis of Bioequivalence Study Reports Between 2013 and 2019

Abstract: Demonstration of bioequivalence (BE) is mandatory while developing generic drugs. The scientific concept of BE applies equally to different regulatory agencies. However, the application of the concept may differ for each agency, which can affect the design of BE studies. To evaluate the study practices in terms of the BE concept in South Korea, we retrospectively analyzed BE study reports available from Ministry of Food and Drug Safety between 2013 and 2019. Statistical estimation of the pharmacokinetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
5
0
2
Order By: Relevance
“…Several design aspects of the accepted bioequivalence trials in our study share similarities with those submitted to other regulators [13,14,19]. This similarity can be attributed to the common adoption of a 2 × 2 crossover Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Several design aspects of the accepted bioequivalence trials in our study share similarities with those submitted to other regulators [13,14,19]. This similarity can be attributed to the common adoption of a 2 × 2 crossover Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The extracted CVws from the accepted trials (for both single APIs and fixed combinations) were assessed in relation to the trial sample size , trial design, and the different BCS classes (the recent Korean review found that highly variable drugs are mostly BCS Class II or IV [i.e. drugs with poor solubility]) [14]. Reasons for rejecting the submission of bioequivalence trials or for rejecting their results were explored in addition to the success rate of study centers per country.…”
Section: Study Outcomes and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As more than half of the phase 1 trials were associated with fixed combination drugs or new formulations of marketed drugs in Korea [ 19 ], the trends of clinical trials could be influenced by several popular drug classes. Similarly, bioequivalence trials highly focused in several therapeutic areas were reported in another study [ 20 ].…”
Section: Discussionmentioning
confidence: 82%
“…A generic drug is one whose active ingredients are equivalent to those of the original drug (also known as the reference or brand-name drug), has passed bioequivalence testing, and has been approved by regulatory authorities for interchangeable applications with the original drug [ 1 3 ]. Generics typically enter the market at a lower price than that of the original drugs; therefore, they provide numerous benefits such as reduced healthcare costs and enhanced patient access to medical care.…”
Section: Introductionmentioning
confidence: 99%